Gut Microbiome as a Potential Biomarker in Fish: Dietary Exposure to Petroleum Hydrocarbons and Metals, Metabolic Functions and Cytokine Expression in Juvenile Lates calcarifer - Spilsbury, Francis; Foysal, Md Javed; Tay, Alfred; Gagnon, Marthe Monique (Frontiers in Microbiology, 2022)
The gut microbiome of fish contains core taxa whose relative abundances are modulated in response to diet, environmental factors, and exposure to toxicogenic chemicals, influencing the health of the host fish. Recent advances in genomics and metabolomics have suggested the potential of microbiome analysis to be a biomarker for exposure to toxicogenic compounds. In this 35-day laboratory study, 16S RNA sequencing and multivariate analysis was used to explore changes in the microbiome of juvenile Lates calcarifer exposed to dietary sub-lethal doses of three metals: vanadium (20mg/kg), nickel (480mg/kg) and iron (470mg/kg); and to two oils : bunker C heavy fuel oil (1%w/w), and Montara, a typical Australian medium crude oil (1%w/w). Diversity of the gut microbiome was significantly reduced compared to negative controls in fish exposed to metals, but not petroleum hydrocarbons. The core taxa in the microbiome of negative control fish was comprised of phyla Proteobacteria (62%), Firmicutes (7%), Plantomycetes (3%), Actinobacteria (2%), Bacteroidetes (1%) and others (25%). Differences in the relative abundances of bacterial phyla of metals exposed fish were pronounced, with the microbiome of Ni-, V- and Fe-exposed fish dominated by Proteobacteria (81%), Firmicutes (68%) and Bacteroidetes (48%) respectively. The genus Photobacterium was enriched proportionally to the concentration of polycyclic aromatic hydrocarbons (PAHs) in oil-exposed fish. The probiotic lactic acid bacteria, Lactobacillus was significantly reduced in the microbiota of fish exposed to metals. Transcription of cytokines IL-1, IL-10 and TNF-a were significantly up-regulated in fish exposed to metals, but unchanged in oil exposed fish compared to negative controls. However, IL-7 was significantly down-regulated in fish exposed to V, Ni, Fe and heavy fuel oil. Fish gut microbiome exhibits distinctive changes in response to specific toxicants, and show potential for use as biomarkers of exposure to V, Ni, Fe and to PAHs present in crude oil.